Allelopathic effect of eichhornia crassipes aqueous extract against growth of mimosa pudica - Arofah Laemah,; Waewruedee Waewthongrak, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Allelopathy is a phenomenon in which a plant produces allelochemicals that affect neighboring plants’ growth and physiological processes. This study aimed to investigate the allelopathic effect of Eichhornia crassipes on the growth of Mimosa pudica seedlings. The experiment was conducted in the pot, where M. pudica seedlings were irrigated with aqueous leaf extract of E. crassipes at 5, 10 and 15% (w/v) concentrations once a week for four consecutive weeks. The experiment was carried out by Completely Randomized Design (CRD) with three replicates. The allelochemical contents of leaf extract were quantified using a spectrophotometric method, and the total phenolic content was 129.54 mg GAE/g DW. The maximum percentage of electrolyte leakage was detected in M. pudica seedlings when treated with a higher concentration of E. crassipes leaf extract. The allelopathic effect of E. crassipes extract on growth, chlorophyll content and lipid peroxidation was also determined. The result showed a significant decrease in length, weight and chlorophyll contents treated with 10 and 15% concentrations of E. crassipes leaf extracts. However, malondialdehyde (MDA) in the root of M. pudica seedlings treated with aqueous leaf extract of E. crassipes at 10% and 15% (w/v) concentrations were found to be remarkably higher compared to control. These results indicated that the E. crassipes leaf extract exhibited allelopathic effects on M. pudica growth. However, the increase of the allelopathic effect of E. crassipes leaf extract was concentration-dependent.